Handover algorithm with joint processing technique based on coordinated multipoint (COMP) transmission and reception in LTE-advanced heterogeneous network / Muhammad Aiman Zainali - Zainali, Muhammad Aiman (2020)
In mobile network, mobility management plays an important role in order to support seamless handover in Long Term Evolution-Advanced (LTE-A) network. LTE-A is the new technology that has become one of the important parts of every day’s life and for the future concerning heterogeneous network. It is predicted that in the near future there will be an increase demand of voice traffic and data traffic. One of the important parts in communication is handover execution. Currently, LTE-A network purely depends on the hard handover that may cause disconnection to occur if the handover is not fast enough. Thus, it is important to optimize some technique and specific service to the mobile users in order to improve the handover execution. There exist some limitations on the hard handover, such as high data loss, disruption time and high outages thus causing an unreliable handover procedure. In addition, by using hard handover technique, it will be difficult to maintain the QoS requirement due to the delay in handover that commonly occurs during eNB migration. The most promising technique in LTE-A network to cope with this problem is by using the Joint Processing (JP) Technique based Coordinate Multipoint (CoMP) Transmission and Reception. With this technique, each UE connected with the source eNB with a single connection for any time instant that restricted by the nature of hard handover mechanism. Therefore, when the concept of JP in CoMP allowing multiple data transmissions for each UE at any time instant comes in LTE-A system, it becomes conflicted with the concept of standard hard handover mechanism. To solve this problem, it is necessary to have a proper handover algorithm. When handover executes, it may experience failure because of the early handover, the late handover or handover to wrong cell. Thus, the cases of packet loss or communication interruption problems will occur. In this research, a JP based on CoMP handover algorithm in LTE-A network is proposed. Firstly, a formulation of analytical framework has been proposed to analyze the handover performance. Then, mathematical equations have been derived from the proposed framework by incorporating the value of user’s speed and handover signaling delay in adaptive Reference Signal Received Power (RSRP) threshold. Under this framework, the probabilities of handover failure were analyzed in order to observe the relationship between both macro and femto handover when the speed of user increased. From the result, it has been found that with the proposed framework, an adaptive RSRPth value for handover initiation has been identified. The numerical results show that the proposed framework able to reduce the probability of handover failure up to 98%. The JP technique based on CoMP handover algorithm has been proposed and the simulation results show a significant reduction in number of handover calls rate up to 68% when compared to other handover algorithm. This shows that the proposed JP based on CoMP handover algorithm was able to reduce the unnecessary handover within the LTE-A heterogeneous network.